Sosialisasi Penerapan prinsip Airmanship di Perusahaan Pengiriman Barang di PT Ardhya Bumi Persada (ABP) - Bambang Widarto; Rizky Karo Karo; Sujono; Supri Abu; G. Magdalena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The Faculty of Law at Dirgantara Marsekal Suryadarma University has successfully conducted a Community Engagement Program (PKM) at PT Ardya Bumi Persada (ABP), emphasizing the critical importance of Airmanship. Staff members now possess a comprehensive understanding that Airmanship encompasses not only inspection and oversight but also strict legal compliance pertaining to aviation safety. Through the implemented methodology of socialization and legal counseling, PT ABP is now equipped to conduct its business operations with elevated safety standards for both its general operations and the shipment of goods, thereby enhancing public trust and bolstering the company's reputation. Through this Community Engagement Program (PKM), ABP staff have gained a deeper understanding of the significance of airmanship and various international regulations, including the Annexes to the Convention on International Civil Aviation, commonly known as the Chicago Convention of 1944, particularly concerning the process of air cargo transportation.